Metabolites Profiling of Soil Actinomycetes with Antimicrobial and Anticancer Activities - Ram Prabodh Yadav; Bibek Raj Bhattarai; Rabin Budhathoki; Padamlal Budthapa; Monika Rana; Rubin Thapa Magar; Bijaya Bahadur Thapa; Akkal Dev Mishra; Niranjan Parajuli (Nepal Journal of Biotechnology, 2024)
Metabolic profiling of actinomycetes isolated from Nepalese soil has uncovered promising candidates for the development of new antimicrobial and anticancer agents. This research examines the potential of actinobacteria isolated from soil, namely strains PY40, PY118, and PY122, as promising sources for biological applications. These strains were identified using 16S rRNA gene sequencing as Streptomyces sp. PY40, Streptomyces sp. PY118, and Amycolatopsis sp. PY122. Comprehensive bioassays were carried out on ethyl acetate (EA) extract originating from the fermentation broths of these species to assess their antimicrobial and anticancer activities. The results showed noteworthy antifungal and anticancer properties of Streptomyces sp. PY40 extract, thereby indicating its possible use in the synthesis of pharmaceuticals. Furthermore, potent antifungal activity was observed with an extract from Amycolatopsis sp. PY122. These isolates showed strong inhibition against several multi-drug-resistant strains of bacteria, including Shigella sonnei ATCC 25931, Klebsiella pneumoniae ATCC 700603, Escherichia coli ATCC 25922, and, Staphylococcus aureus ATCC 43300, suggesting significant antibacterial activity of the extracts. Gas Choursomatography-Mass Spectrometry (GC-MS) analysis revealed particularly volatile chemical constituents in the extracts. Antibiotic agents such as diketopiperazines and hexahydropyrrolo[1,2-a]pyrazine-1,4-dione were prevalent in the extracts of these isolates. This study enhances our comprehension of the bioactive potential of these microorganisms and underscores their value as a source for creating novel therapeutics to address multi-resistant infections and cancer demands. These findings show that actinomycetes from Nepalese soil have high prospects for biological applications.